Intelectuais e Comunismo no Brasil (Dialogos, 2017)
Resenha do livro: RODRIGUES, Cândido Moreira; BARBOSA, Jefferson Rodrigues (Orgs.). Intelectuais e Comunismo no Brasil: 1920-1950. Cuiabá: EdUFMT, 2011, 154 p.